Pengaruh Terapi Al-Qurani dalam Konseling Islam terhadap Perilaku Kecanduan Film Pornografi pada Remaja Laki-laki di Surabaya - Muh. Yusran Diniy; Shella Satiwi Guci (Medan Resource Center, 2025)
Pornography addiction is a form of deviant behavior that adversely affects the mental, spiritual, and social well-being of adolescents. This study aims to examine the effectiveness of Islamic counseling employing Qur’anic recitation therapy in reducing pornography-viewing addiction among a young male in Surabaya. Using a qualitative approach, data were collected through observation, interviews, and documentation, followed by a comparative descriptive analysis of the client’s condition before and after the therapeutic intervention. The findings reveal a substantial decrease in the frequency of pornography consumption after the client underwent a structured Qur’anic recitation program. The client, who previously viewed pornographic films 3–7 times per week, showed a marked decline to only once every two weeks. Improvements were also observed in self-control, daily habits, and the development of more religious attitudes. These results demonstrate that Islamic counseling integrated with Qur’anic therapy can serve as an effective alternative for assisting individuals in overcoming pornography addiction while fostering healthier behaviors aligned with Islamic values.